Upregulation of anti-oxidative stress response improves metabolic changes in L-selectin-deficient mice but does not prevent NAFLD progression or fecal microbiota shifts - Eswaran, Sreepradha; Babbar, Anshu; Drescher, Hannah K.; Hitch, Thomas C. A.; Clavel, Thomas; Muschaweck, Moritz; Ritz, Thomas; Kroy, Daniela C.; Trautwein, Christian; Wagner, Norbert; Schippers, Angela (International journal of molecular sciences, 2021)
(1) Background: Non-alcoholic fatty liver disease (NAFLD) is a growing global health problem. NAFLD progression involves a complex interplay of imbalanced inflammatory cell populations and inflammatory signals such as reactive oxygen species and cytokines. These signals can derive from the liver itself but also from adipose tissue or be mediated via changes in the gut microbiome. We analyzed the effects of a simultaneous migration blockade caused by L-selectin-deficiency and an enhancement of the anti-oxidative stress response triggered by hepatocytic Kelch-like ECH-associated protein 1 (Keap1) deletion on NAFLD progression. (2) Methods: L-selectin-deficient mice (Lsel−/−Keap1flx/flx) and littermates with selective hepatic Keap1 deletion (Lsel−/−Keap1Δhepa) were compared in a 24-week Western-style diet (WD) model. (3) Results: Lsel−/−Keap1Δhepa mice exhibited increased expression of erythroid 2-related factor 2 (Nrf2) target genes in the liver, decreased body weight, reduced epidydimal white adipose tissue with decreased immune cell frequencies, and improved glucose response when compared to their Lsel−/−Keap1flx/flx littermates. Although WD feeding caused drastic changes in fecal microbiota profiles with decreased microbial diversity, no genotype-dependent shifts were observed. (4) Conclusions: Upregulation of the anti-oxidative stress response improves metabolic changes in L-selectin-deficient mice but does not prevent NAFLD progression and shifts in the gut microbiota.